Protective effects of melatonin as a free radical scavenger in the formation of gastric ulcer: a light and scanning electron microscope study - (:unkn) unknown (Found Adv Med Sci Inc, Mahwah, NJ, United States, 2000)
A study was carried out to investigate the cytoprotective role of melatonin by comparing its protective effect against salicylate induced gastric lessions with that of omeprazole and famotidine. Gastric acidity, gastric tissue glutathione, lipid peroxidation and myeloperoxidase leves were determined in gastric tissue of wistar albino rats. Tissue sections were investigated by light and scanning electron microscopes. The results indicate that active oxygen species and lipid peroxidation have an important role in the formation of gastric mucosal damage caused by acetyl salycilic acid and both omeprazole and famotidine may protect the gastric tissue against this damage.